2021
DOI: 10.3389/feduc.2021.693355
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Reality to Assess Reading Fluency in Children

Abstract: Here we provide a proof-of-concept for the use of virtual reality (VR) goggles to assess reading behavior in beginning readers. Children performed a VR version of a lexical decision task that allowed us to record eye-movements. External validity was assessed by comparing the VR measures (lexical decision RT and accuracy, gaze durations and refixation probabilities) to a gold standard reading fluency test—the One-Minute Reading test. We found that the VR measures correlated strongly with the classic fluency mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Nevertheless, two studies that used VR as a means to assess reading fluency have been carried out. In one recent study, Mirlaut et al used VR glasses to assess beginner reading behavior and to measure their RF with the One-Minute Reading test [35]. While this study focused on native speakers, it showed that VR could be used as a legitimate tool for studying reading behavior in general terms [35].…”
Section: Vr and Learningmentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, two studies that used VR as a means to assess reading fluency have been carried out. In one recent study, Mirlaut et al used VR glasses to assess beginner reading behavior and to measure their RF with the One-Minute Reading test [35]. While this study focused on native speakers, it showed that VR could be used as a legitimate tool for studying reading behavior in general terms [35].…”
Section: Vr and Learningmentioning
confidence: 95%
“…In one recent study, Mirlaut et al used VR glasses to assess beginner reading behavior and to measure their RF with the One-Minute Reading test [35]. While this study focused on native speakers, it showed that VR could be used as a legitimate tool for studying reading behavior in general terms [35]. As part of a master's thesis, the impact of reading in VR on a group of dyslexic student's reading fluency was explored [36].…”
Section: Vr and Learningmentioning
confidence: 99%